Two-component polyurethane heat-conducting structural adhesive and preparation method thereof

A two-component formulation of modified polyester polyol and surface-treated thermally conductive filler was developed to produce a high-strength, high-toughness, and excellent thermal conductivity polyurethane thermally conductive structural adhesive, which solves the heat dissipation and protection problems of new energy vehicle batteries.

CN119264862APending Publication Date: 2025-01-07KEJIAN POLYMER MATERIALS (SHANGHAI) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411581238.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing polyurethane adhesives used in new energy vehicle batteries suffer from poor thermal conductivity and insufficient toughness, making it difficult to meet the battery's heat dissipation requirements and failing to provide effective protection in vibration environments.

Method used

A polyurethane thermally conductive structural adhesive with good flowability, high strength, high adhesion and flame retardancy was prepared by using modified polyester polyol, blocked polyurethane prepolymer and surface-treated thermally conductive filler in combination with a two-component formulation.

Benefits of technology

The thermal conductivity of the polyurethane adhesive has been improved, and it possesses high strength and toughness, enabling effective heat dissipation and battery protection, while adapting to the vibration environment of automobiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005123158020000041
    Figure BDA0005123158020000041
  • Figure BDA0005123158020000051
    Figure BDA0005123158020000051
  • Figure BDA0005123158020000061
    Figure BDA0005123158020000061
Patent Text Reader

Abstract

The invention relates to the field of new energy automobile batteries, and discloses a two-component polyurethane heat-conducting structural adhesive and a preparation method thereof. The structural adhesive comprises a component A and a component B in a volume ratio of 1: 1, the component A is prepared from 15 to 25 parts of modified polyester polyol; 5 to 10 parts of polyether polyol; 3-8 parts of a chain extender; 55-67 parts of a modified heat-conducting filler; 0.2 to 0.5 part of a dispersing aid I; 0.1 to 0.3 part of black paste; 0.3 to 1 part of a thixotropic agent; 1-5 parts of a dewatering agent; the component B comprises the following components in parts by weight: 30-50 parts of a blocked polyurethane prepolymer; 45-67 parts of a modified heat-conducting filler; 0.2-1 part of a dispersing aid I; 0.2 to 0.5 part of a dispersing aid II; 0.2 to 0.5 part of a defoaming agent; and 0.2 to 1 part of a dewatering agent. The polyurethane heat-conducting structural adhesive disclosed by the invention not only has good mechanical properties, but also has good heat-conducting and flame-retardant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of new energy vehicle batteries, and more specifically, to a two-component polyurethane thermal conductive structural adhesive and a preparation method thereof. Background Art

[0002] In recent years, with the progress and demand of social science and technology, the development of new energy vehicles has rapidly increased from 705.8 and 688.7 in 2022 to 9.587 million and 9.495 million in 2023, an increase of 35.8% and 37.9% respectively. The rapid development of the industry promotes the development and improvement of related industries. Because the surface material of the power battery PACK module includes PET, PC, aluminum alloy and other functional materials, the structural adhesive is required to have good adhesion and coating on various materials without surface treatment. At the same time, with the continuous upgrading and iteration of power battery technology, the heat dissipation problem of soft pack battery cells has become increasingly prominent, so the thermal conductivity and flow performance of two-component polyurethane adhesives are required to be higher and higher.

[0003] Polyurethane is a block copolymer containing soft segments and hard segments, which has the advantages of good wear resistance, water resistance, oil resistance and solvent resistance. By adjusting the hard segment content and the composition of the soft segment, the tensile strength and elongation at break of the material can be flexibly controlled to achieve a balance between strength and toughness. However, the thermal conductivity of polyurethane itself is not high, only 0.1-0.3W / m·K, which leads to poor heat dissipation performance and makes it difficult to meet the heat dissipation requirements of electrical and electronic equipment, thereby affecting the reliability and service life of the equipment. Although filling thermal conductive fillers can effectively improve the thermal conductivity of the material, it usually sacrifices the mechanical strength and toughness of the material, which seriously limits its application and development. Since the car will vibrate for a long time during operation, it is not only necessary for the adhesive to have high bonding strength, but more importantly, it must have good toughness, so as to play a role in buffering and protecting the battery. Therefore, for the bonding application of automotive power batteries, the adhesive must not only have high thermal conductivity, but also high strength, high bonding, high toughness and other characteristics. However, most of the current research on thermal conductive structural adhesives focuses on improving strength, while ignoring the toughness (the ability of the material to absorb energy during plastic deformation). If a material only pursues high strength without proper toughness, it is of little practical use. Therefore, it is very important to provide an adhesive with good thermal conductivity, flame retardancy, and good strength and toughness. Summary of the invention

[0004] In order to solve the problems in the prior art, the present application provides a two-component polyurethane thermal conductive structural adhesive and a preparation method thereof. The thermal conductive structural adhesive of the present application has low viscosity and good fluidity. It is not only convenient to coat on the surface of the battery, but also can be in closer contact with the surface of the battery. It is not only heat-conductive and flame-retardant, but also has high strength, high adhesion, and excellent mechanical properties.

[0005] In a first aspect, the present application provides a two-component polyurethane thermally conductive structural adhesive, comprising a component A and a component B in a volume ratio of 1:1;

[0006] Calculated by weight, the component A comprises:

[0007] Modified polyester polyol 15-25 parts; polyether polyol 5-10 parts; chain extender 3-8 parts; modified thermal conductive filler 55-67 parts; dispersing aid 0.2-0.5 parts; black paste 0.1-0.3 parts; thixotropic agent 0.3-1 parts; defoamer 0.2-0.5 parts; dewatering agent 1-5 parts;

[0008] Calculated by weight, the component B comprises:

[0009] 30-50 parts of blocked polyurethane prepolymer; 45-67 parts of modified thermal conductive filler; 0.2-1 parts of dispersing aid 1; 0.2-0.5 parts of dispersing aid 2; 0.2-0.5 parts of defoaming agent; 0.2-1 parts of water removing agent.

[0010] Preferably, the modified polyester polyol is one or more of polyethylene adipate glycol ester diol, polypropylene adipate glycol ester diol, polyethylene adipate glycol ester diol, 1,6-hexanediol phthalate glycol ester diol, diethylene phthalate glycol ester diol, polyester diol and polycarbonate diol.

[0011] More preferably, the modified polyester polyol has a molecular weight of 800-3000, a functionality of 2-3, and a hydroxyl value of 160-165.

[0012] Preferably, the polyether polyol is selected from one or more of polyoxypropylene glycol PPG1000, PPG2000 and polyoxypropylene triol.

[0013] More preferably, the polyether polyol has a molecular weight of 1000-2000, a functionality of 2-3, and a hydroxyl value of 160-165.

[0014] Preferably, the chain extender is one or more of 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,2-hexanediol, 1,3-hexanediol, and 2,4-trimethyl-1,3-pentanediol.

[0015] Preferably, the modified thermally conductive filler is one or more of aluminum hydroxide, aluminum oxide, aluminum nitride or magnesium hydroxide.

[0016] More preferably, the particle size of the thermally conductive filler is 150 μm, and the shape of the thermally conductive filler is one or more of spherical, quasi-spherical, and flake.

[0017] More preferably, the thermally conductive filler is surface-modified aluminum hydroxide alpha powder, wherein the particle size D50 is 1 μm to 50 μm, and the free water content of the powder is ≤0.2%.

[0018] Preferably, the dispersing aid 1 is one of BYK-P104S, BYK-P104, BYK-101, BYK-103, BYK-107, and BYK-108.

[0019] Preferably, the dehydrating agent is one or more of p-toluenesulfonyl isocyanate, molecular sieves, vinyltrimethoxysilane, methyltrimethoxysilane or carbamate-bridged bis-oxazolidine.

[0020] Preferably, the closed polyurethane prepolymer is a prepolymer obtained by pre-reaction of MDI.

[0021] Preferably, the second dispersing aid is benzoyl chloride.

[0022] Preferably, the defoaming agent is one or more of BYK019, BYK065, BYK535, and BYK066.

[0023] In a second aspect, the present application provides a method for preparing the two-component polyurethane thermally conductive structural adhesive described in the first aspect, comprising the following steps:

[0024] Step S1, preparing component A:

[0025] Step S2, preparing a blocked polyurethane prepolymer:

[0026] Step S3, preparing component B:

[0027] Step S4, mixing the component A and the component B in a volume ratio of 1:1 to obtain a two-component polyurethane thermal conductive structural adhesive.

[0028] Furthermore, the step S1 includes the following steps:

[0029] Step S11: adding modified polyester polyol, polyether polyol, chain extender, dispersing aid and defoamer into a reaction kettle, stirring evenly, and stirring at 105-110° C. for 1.5 h-2 h;

[0030] Step S12: Cooling to 70-80° C., adding modified thermal conductive filler and thixotropic agent, and stirring at high speed for 1-1.5 hours until no particles are left;

[0031] Step S13: Add dewatering agent, defoaming agent and black slurry and stir thoroughly for 0.5-1h to obtain the component A.

[0032] Furthermore, the step S2 comprises the following steps:

[0033] Step S21: heat the polyether polyol in a 500 mL three-necked flask equipped with a stirrer and a thermometer, start stirring, heat up and evacuate, dehydrate at 105-110° C. and vacuum degree 133 Pa for 2 h, then cool to below 50° C., place in a dry container and seal for storage for later use;

[0034] Step S22: Add polyether polyol and diisocyanate in a dry three-necked flask according to the formula amount, stir evenly and heat to 75-80° C.; stir evenly for 3-4 hours and then add a sealing agent and stir for another 20 minutes to obtain a blocked polyurethane prepolymer.

[0035] Furthermore, step S3 includes the following steps:

[0036] Step S31: adding the blocked polyurethane prepolymer, defoamer, dispersing aid 1 and dispersing aid 2 prepared in S2 into a reaction kettle and stirring at a constant speed for 20-30 minutes;

[0037] Step S32: Add the modified thermal conductive filler and the dehydrating agent and stir thoroughly for 1-2 hours to obtain component B.

[0038] In summary, compared with the prior art, the polyurethane thermal conductive structural adhesive of the present invention not only has good mechanical properties, but also has good thermal conductivity and flame retardant properties, as follows:

[0039] (1) By adding modified polyester polyols, due to the characteristics of the benzene ring structure, on the one hand, it is beneficial to enhance the cohesive force of the matrix, thereby improving the mechanical properties of the material. On the other hand, it improves the adhesion of the glue, and at the same time, it also improves the flame retardant properties of the structural adhesive.

[0040] (2) Utilizing the excellent stability of the blocked polyurethane prepolymer, the prepared component B has excellent storage stability, and the viscosity of component B will not increase significantly even if stored for a long time.

[0041] (3) The use of two dispersants in combination significantly reduces the viscosity of component B, solving the problem of poor fluidity and difficulty in coating.

[0042] (4) The thermal conductivity of the mixed glue is significantly improved by the surface-treated thermal conductive powder. DETAILED DESCRIPTION

[0043] The technical scheme and effects of the present application are further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the invention, rather than to limit the invention.

[0044] In the following examples and comparative examples, the raw materials used are commercially available unless otherwise specified.

[0045] raw material:

[0046]

[0047] Example 1

[0048] The raw materials and proportions in the examples are shown in the table below, and are prepared by the following method:

[0049] Step S1, preparing component A:

[0050] Step S11: adding modified polyester polyol, polyether polyol, chain extender and dispersing aid into a reaction kettle, stirring evenly, and stirring at 105° C. for 2 h;

[0051] Step S12: Cooling to 75° C., adding modified thermal conductive filler and thixotropic agent, and stirring at high speed for 1.5 hours until no particles are left;

[0052] Step S13: adding a dewatering agent, a defoaming agent and a black slurry and stirring them thoroughly for 1 hour to obtain the component A.

[0053] Step S2, preparing a blocked polyurethane prepolymer:

[0054] Step S21: heat the polyether polyol in a 500 mL three-necked flask equipped with a stirrer and a thermometer, start stirring, heat up and evacuate, dehydrate at 105° C. and a vacuum degree of 133 Pa for 2 h, then cool to below 50° C., place in a dry container and seal for storage for later use;

[0055] Step S22: Add 24.5 parts of polyoxypropylene diol, 40.2 parts of polyoxypropylene triol, 110.144 parts of diisooctyl phthalate, and 0.01 parts of toluenesulfonyl isocyanate to a dry three-necked flask, and stir and mix under vacuum at 50°C to 55°C for 20 minutes, wherein the vacuum degree is ≤-0.09MPa. Nitrogen is depressurized, wherein the nitrogen purity is ≥95%, 13 parts of diphenylmethane-4,4'-diisocyanate and 0.002 parts of dibutyltin dilaurate are added to the reaction mixture of the step, respectively, and the addition is controlled within 5 minutes, and the temperature is raised by vacuum stirring, wherein the heating rate is 10°C / 10min, and the vacuum degree is ≤-0.09MPa. After reacting for 1.5 hours at a temperature of 65°C±2°C, NCO reaches a preset target of ≤20.95%, and the heating and insulation equipment are turned off. The pressure was released by nitrogen, wherein the purity of nitrogen was ≥95%. 110.144 parts of diisooctyl phthalate and 10 parts and 2 parts of blocking agent (methyl ethyl ketone oxime) were added to the reaction mixture at room temperature. The mixture was stirred in vacuum for 10 minutes. The reaction mixture was cooled to below 50°C. The pressure was released by nitrogen and the material was discharged. After the material was discharged, it was sealed and stored with nitrogen. The final NCO was 20.51%.

[0056] Step S3, preparing component B:

[0057] Step S31: adding the blocked polyurethane prepolymer, defoamer and dispersing agent 2 prepared in S2 into a reaction kettle and stirring at a constant speed for 30 minutes;

[0058] Step S32: adding the modified thermal conductive filler and the dehydrating agent and stirring them thoroughly for 2 hours to obtain component B.

[0059] Step S4, mixing the component A and the component B in a volume ratio of 1:1 to obtain a two-component polyurethane thermal conductive structural adhesive.

[0060]

[0061]

[0062] Comparative Example 1

[0063] The difference from Example 1 is that the raw materials and proportions in the comparative example are as shown in the following table.

[0064]

[0065] The common polyether polyol in Comparative Example 1 does not have a benzene ring and cannot meet the strength requirements of the structural adhesive and the adhesion to the substrate.

[0066] Comparative Example 2

[0067] The difference from Example 1 is that the raw materials and proportions in the comparative example are as shown in the following table.

[0068]

[0069]

[0070] In Comparative Example 2, the dispersing effect of the dispersant RHEOBYK-108 on the component B is far inferior to that of benzoyl chloride, so that the viscosity of the component B is too high and it cannot flow, and it cannot coat the substrate well.

[0071] Comparative Example 3

[0072] The difference from Example 1 is that the raw materials and proportions in the comparative example are as shown in the following table.

[0073]

[0074]

[0075] The thermal conductivity of the thermal conductive powder without surface treatment in Comparative Example 3 is low, which cannot meet the thermal conductivity requirements, and the flame retardant effect is not good.

[0076] Comparative Example 4

[0077] The difference from Example 1 is that the raw materials and proportions in the comparative example are as shown in the following table.

[0078]

[0079] In Comparative Example 4, the terminal isocyanate in the common isocyanate 44v20 is relatively active, so the storage stability is low, and the viscosity of component B increases with the storage time.

[0080] Comparative Example 5

[0081] The difference from Example 1 is that the raw materials and proportions in the comparative example are as shown in the following table.

[0082]

[0083]

[0084] In Comparative Example 5, appropriate addition of aluminum nitride can further improve thermal conductivity and flame retardancy.

[0085] Performance Testing

[0086] Detection method:

[0087] 1. Viscosity: GB / T 2794-2013, test temperature 25°C, 7# rotor;

[0088] 2. Flame retardant: UL-94, UL94 horizontal and vertical combustion test chamber;

[0089] 3. Thermal conductivity: ASTM5470, interface material thermal conductivity tester;

[0090] 4. Tensile shear strength: GB / T7124-2008;

[0091] 5.Peel strength: GB / T2792-2014.

[0092] Test results:

[0093]

[0094]

[0095] In summary, compared with the prior art, the polyurethane thermal conductive structural adhesive of the present invention not only has good mechanical properties, but also has good thermal conductivity and flame retardant properties.

[0096] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A two-component polyurethane thermal conductive structural adhesive, characterized in that: It includes component A and component B in a volume ratio of 1:1; Calculated by weight, the component A comprises: Modified polyester polyol 15-25 parts; polyether polyol 5-10 parts; chain extender 3-8 parts; modified thermal conductive filler 55-67 parts; dispersing aid 0.2-0.5 parts; black paste 0.1-0.3 parts; thixotropic agent 0.3-1 parts; defoamer 0.2-0.5 parts; dewatering agent 1-5 parts; Calculated by weight, the component B comprises: 30-50 parts of blocked polyurethane prepolymer; 45-65 parts of modified thermal conductive filler; 0.2-1 parts of dispersing aid 1; 0.2-0.5 parts of dispersing aid 2; 0.2-0.5 parts of defoaming agent; 0.2-1 parts of water removing agent.

2. The two-component polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The modified polyester polyol is one or more of polyethylene adipate glycol, polypropylene adipate glycol, polyethylene adipate glycol butanediol, 1,6-hexanediol phthalate, diethylene glycol phthalate, polyester diol and polycarbonate diol; The polyether polyol is selected from one or more of polyoxypropylene glycol PPG1000, PPG2000 and polyoxypropylene triol; The chain extender is one or more of 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,2-hexanediol, 1,3-hexanediol, and 2,4-trimethyl-1,3-pentanediol; The modified thermal conductive filler is one or more of aluminum hydroxide, aluminum oxide, aluminum nitride or magnesium hydroxide; The first dispersing aid is one of BYK-P104S, BYK-P104, BYK-101, BYK-103, BYK-107, and BYK-108; The dewatering agent is one or more of p-toluenesulfonyl isocyanate, molecular sieve, vinyltrimethoxysilane, methyltrimethoxysilane or carbamate-bridged bis-oxazolidine; The closed polyurethane prepolymer is a prepolymer obtained by pre-reaction of MDI; The second dispersing aid is benzoyl chloride; The defoaming agent is one or more of BYK019, BYK065, BYK535 and BYK066.

3. The two-component polyurethane thermal conductive structural adhesive according to claim 2, characterized in that: The modified polyester polyols have a molecular weight of 800-3000, a functionality of 2-3, and a hydroxyl value of 160-165.

4. The two-component polyurethane thermal conductive structural adhesive according to claim 2, characterized in that: The polyether polyol has a molecular weight of 1000-2000, a functionality of 2-3, and a hydroxyl value of 160-165.

5. The two-component polyurethane thermal conductive structural adhesive according to claim 2, characterized in that: The particle size of the thermal conductive filler is 150 μm, and the shape of the thermal conductive filler is one or more of spherical, quasi-spherical, and flake.

6. The two-component polyurethane thermal conductive structural adhesive according to claim 5, characterized in that: The thermal conductive filler is surface-modified aluminum hydroxide alpha powder, wherein the median diameter D50 is 1 μm to 50 μm, and the free water content of the powder is ≤0.2%.

7. The method for preparing the two-component polyurethane thermal conductive structural adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step S1, preparing component A: Step S2, preparing a blocked polyurethane prepolymer: Step S3, preparing component B: Step S4, mixing the component A and the component B in a volume ratio of 1:1 to obtain a two-component polyurethane thermal conductive structural adhesive.

8. The method for preparing the two-component polyurethane thermal conductive structural adhesive according to claim 7, characterized in that: The step S1 comprises the following steps: Step S11: adding modified polyester polyol, polyether polyol, chain extender, dispersing aid and defoamer into a reaction kettle, stirring evenly, and stirring at 105-110° C. for 1.5 h-2 h; Step S12: Cooling to 70-80° C., adding modified thermal conductive filler and thixotropic agent, and stirring at high speed for 1-1.5 hours until no particles are left; Step S13: Add dehydrating agent and black slurry and stir thoroughly for 0.5-1h to obtain the component A.

9. The method for preparing the two-component polyurethane thermal conductive structural adhesive according to claim 7, characterized in that: The step S2 comprises the following steps: Step S21: heat the polyether polyol in a 500 mL three-necked flask equipped with a stirrer and a thermometer, start stirring, heat up and evacuate, dehydrate at 105-110° C. and vacuum degree 133 Pa for 2 h, then cool to below 50° C., place in a dry container and seal for storage for later use; Step S22: Add polyether polyol and diisocyanate in a dry three-necked flask according to the formula amount, stir evenly and heat to 75-80° C.; stir evenly for 3-4 hours and then add a sealing agent and stir for another 20 minutes to obtain a blocked polyurethane prepolymer.

10. The method for preparing the two-component polyurethane thermal conductive structural adhesive according to claim 7, characterized in that: The step S3 comprises the following steps: Step S31: adding the blocked polyurethane prepolymer, defoamer and dispersing aid prepared in S2 into a reaction kettle and stirring at a constant speed for 20-30 minutes; Step S32: Add the modified thermal conductive filler and the dehydrating agent and stir thoroughly for 1-2 hours to obtain component B.

Citation Information

Cited By

  • Two-component polyurethane heat-conducting structural adhesive as well as preparation method and application thereof

    CN121574700A